(untitled) (Bangladesh Journal of Neurosurgery, 2024)
Medical education is undergoing significant changes each day in different corners of the world. Calls from different stakeholders for a change in the instructional methods have resulted in innovative medical curriculum. The new curriculum stresses the importance of proficiency in several clinical skills by medical students rather than mere acquisition of knowledge. Teaching and training using simulation technique is very powerful. It provides valuable opportunities to learn and practice the key competencies in medical education, such as communication, problem-solving, teamwork, and leadership as well as management skills such as physical examination, diagnostic and surgical procedures. Pedagogical innovations like simulation-based teaching needs to be brought to the forefront in clinical education in our country. Simulation programs may function well from a technical point of view, but they are often difficult to fit into a curriculum, especially in low-resource settings, where money and technical-know-how are the main limitations. Medical educators have been pushed inevitably to rely on such technology-based learning looking at the future of medical education. However, they should not only embrace it but also develop and evaluate its sustainability and application in preclinical and clinical settings. If well-designed, learning how to operate a simulation program generally requires little effort for them and their students. A short introduction by the teacher is often sufficient to enable the student to work with the program. Bang. J Neurosurgery 2023; 13(1): 24-28